A Review of Ethnomedicinal Uses of Heterophragma Adenophyllum wallich ex. G. Don - Kapdiya, Bhavna B; Patel, Bhupesh; Patel, Bansari S (International Research Journal of Ayurveda & Yoga, 2023)
Background: Heterophragma adenophyllum (wallich ex. G. Don.) is a synonym of Fernandoa adenophylla (Wall. ex. G. Don.) commonly known as Katsagon or Marodphali, belongs to the family Bignoniaceae. The whole plant is considered to be clinically important and used as antidiabetic, amenorrhea, premature ejaculation, night emesis, antimicrobial, antifungal, antiseptic and skin disease. Material And Methods: A present review was carried out to collect all available information on ethnomedicinal claims of Heterophragma adenophyllum (wallich ex. G. Don.) from published literatures, books like Medicinal plants of Gujarat, Reviews on Indian medicinal plants, The wealth of India NISCAIR, etc. also books related to ethnobotany and ethnomedicinal, Google scholar, PubMed, etc. Ethnomedicinal uses of Heterophragma adenophyllum (wallich ex. G. Don.) were collected from all available ethnomedicinal plants-related books, floras, published research articles, etc. Result: It is reported in many states in India, widely distributed at Matheran and Mahabaleshvar in Maharastra, Aasam and Saurastra region of Gujart, Punjab, Tamilnadu, Maharastra, Rajasthan. Its root, leaves, and the whole plant are recommended in 12 different diseases both externally and internally (Table 2). Conclusion: Heterophragma adenophyllum (wallich ex. G. Don.) need to explore with the help of detailed investigation, especially through pharmacological properties. As per ethnomedicinal claims Heterophragma adenophyllum (wallich ex. G. Don.) can be an alternative to Stereospermum suaveolens DC. (Patala).